Evaluasi Interaksi Sosial dan Aksesibilitas Penyandang Disabilitas pada Pelayanan Akademik di Institut Agama Islam Negeri Metro - Sunarwan, Aisyah (Lembaga Penelitian dan Pengabdian kepada Masyarakat of Universitas Islam Negeri Jurai Siwo Lampung, 2018)
The study about empowerment of people with disability is often done by government and social organizations. This can be seen from the publication of the regulation on the fulfillment of the rights of Personal with Disability (PwDs) summarized in Law number 8 of 2016. Previously, children with special needs (disable) get their right of education only in special schools, thus it impacts to social interaction with children who have no obstacles. Inclusive education offers an integrated education model. Inclusive education is conducted to train the interaction of all people from various circles in order to build friendship and association naturally. It also to motivate children who have special needs to be more confident. Through this background the writer conducted research on the interaction process of people with disability and accessibility and academic services at State Institution for Islamic Studies (IAIN) of Metro by using qualitative descriptive method. It is explorative or developmental in interpreting and drawing conclusions. The result of this research is the process of social interaction between PwDs and the academic community runs fairly. The academic service and the fulfillment of the right to education at IAIN Metro are excellent. However, architectural accessibility on the campus of IAIN Metro needs the significant shortcomings that require continuous improvement. So that the IAIN Metro environment can become an educational institution that is friendly to the environment and can realize inclusive education.